David Bayley: a personal reminiscence - Marenin, Otwin (International journal of comparative and applied criminal justice, 2021)
I have known David Bayley personally for a long time and followed his career over the years. David’s reputation and status in the profession rests, I think, on four basic achievements. One was his ability to connect micro level analyses of the police who do policing, as well as other actors on fields of security, to larger national and even global trends. He placed the police squarely into the politics of their locations as powerful political actors. He used democracy in its shifting connotations to judge how well police were performing their job. And he convincingly argued that knowledge gained needed to be used to improve and manage policies.